Causation and responsibility - Moore, Michael S., 1943- (Oxford : Oxford University Press, 2009)
The concept of causation is crucial to ascribing moral and legal responsibility for events. Yet the precise relationship between causation and responsibility remains unclear. This book clarifies that relationship by looking at accounts of causation in metaphysics, and a critique of the confusion in legal doctrine.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Causation; Responsibility